Health Behaviors of Faculty members of Guilan University of Medical Science and ‎their relations with demographic factors - negar puorokhoshvari; afsaneh pasha; atefeh ghanbari; zahra atrkarruoshan; ramesh majdteimuori (Guilan University of Medical Sciences, 2009)
Introduction: Health behaviors are important criteria of health determinants.‎ Objective: This study is carried out to identify health behaviors of Guilan University of Medical ‎Science faculty members and their relations with demographic factors.‎ Methods: In this descriptive correlational study, ‎‏203‏‎ faculty members from Guilan University of ‎Medical Science participated. Data was collected by a two part questionnaire which was self ‎administered. ‎ Results: The research findings revealed that faculty members obtained ‎‏65.9‏‎ percents of health ‎behaviors scores‏.‏‎ There was significant relation between health behaviors with sample's sex ‎‎(P=‎‏0.001‏‎), educational level (P=‎‏0.004‏‎), title (P=‎‏0.034‏‎) and history of chronic diseases (P=‎‏0.036‏‎).‎ Conclusion: In overall, faculty members health behaviors were in average level but their physical ‎activity was poor. Regarding to their modeling role for‏ ‏students, health-promoting programs must be ‎applied for health promotion.‎